Magnetic susceptibility observation of a spin-reorientation transition in Fe/2 ML Ni(111)/W(110) FILMS - Arnold, C.S. (My University, 1997)
One of the most important topics in ultrathin film magnetism is perpendicular ferromagnetism, in which the orientation of the film magnetization is perpendicular to the film plane. A perpendicular orientation is surprising because of the very strong dipolar field produced by the film as a whole which prefers that the film moment be in-plane. In the limit of atomic thicknesses, magnetic anisotropies are occasionally strong enough to overcome the dipolar field and establish a perpendicular orientation of the moment. In such films, the moment exhibits a spin-reorientation transition, reorienting from perpendicular to in-plane with increasing coverage or temperature. Another phenomenon associated with a perpendicular preference is a disintegration of the film into domain structures that are expected to closely resemble liquid crystals. Ultrathin fcc Fe, grown on a 2 atomic layer fcc Ni(111) buffer, is ferromagnetic and exhibits the spin-reorientation transition. Through refinements of an existing technique, the surface magneto-optical Kerr effect (SMOKE), extremely high resolution magnetic susceptibility measurements were made of this system. The magnitudes and temperature-dependencies of the experimental susceptibilities are found to be consistent with theories of the domain structure. A temperature-coverage phase diagram is constructed and reveals structure closer the multicritical point of the transition, where reorientation and order-disorder boundaries meet, than in any previous experimental study. In that part of the phase diagram where the transition to disorder proceeds directly from the perpendicularly magnetized state, no evidence of a Curie temperature is observed.
Keywords: Physics; Physics